A Move Analysis of Abstracts in a Scopus-indexed Applied Linguistics Journal from Different Quartiles - Ashifa Kanafani; Eri Kurniawan; Arif Husein Lubis (RETORIKA: Jurnal Ilmu Bahasa, 2022)
The competitive nature of today’s science leads to the upsurge of publication in scientific journals. Publishing in an international journal with a reputable index such as Scopus, in particular, has gained a significant emphasis. Despite this fact, studies on the rhetorical organization of the abstract section of a research article (RA) through the perspective of Scopus journal quartiles remain scant. Driven by the gap in literature, this study aims to examine whether journal’s quartile affects the rhetorical organization and linguistic realizations of the abstracts. A corpus of 40 RA abstracts was obtained from one Scopus-indexed applied linguistics journal, which over the years, had improvements in terms of its quartiles. The abstracts were divided into three groups: each representing different quartiles of the journal (i.e., Q2, Q3, Q4). Employing a comparative approach using both qualitative and quantitative research methods, Hyland’s (2000) model of rhetorical organization was employed as the main framework to code the rhetorical moves, whereas a statistical analysis (i.e., Z-test) was performed on the moves and steps’ occurrences. The findings showed that there is a significant difference in the steps’ occurrence and tense realization between the groups, indicating that to some extent, the journal’s quartile indeed played a role. The study offers recommendations for further research.